Analisis Faktor-Faktor Kebutuhan dan Peluang Masyarakat Menjadi Nasabah di Bank Syariah Indonesia (BSI) KC Sibolga - Putri Masrifah; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
This study discusses the analysis of the factors of people's needs and opportunities to become customers at Bank Syariah Indonesia (BSI) KC Sibolga. The formulation of the problem raised is